1988
DOI: 10.1177/0893318988001004003
|View full text |Cite
|
Sign up to set email alerts
|

Communication Climate, Job Satisfaction, and Organizational Commitment

Abstract: This study attempted to investigate the effects of communication on organizational commitment (employee loyalty). Based on data from 521 nurses in four general care hospitals, the relationships among three communication variables, four demographic variables, job satisfaction, and organizational commitment were statistically analyzed. The results of the study suggest that communication does affect organizational commitment, that communication affects job satisfaction (employee morale), but that job satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
4

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(36 citation statements)
references
References 28 publications
1
31
0
4
Order By: Relevance
“…Studies reported in the literature have used the COM to test the relationship between communication openness and other organizational variables (Myers et al, 1999;Trombetta & Rogers, 1988). The COM is based on Rogers' model of open communication behaviors that occur in an organizational setting.…”
Section: Assessment Instrumentmentioning
confidence: 99%
“…Studies reported in the literature have used the COM to test the relationship between communication openness and other organizational variables (Myers et al, 1999;Trombetta & Rogers, 1988). The COM is based on Rogers' model of open communication behaviors that occur in an organizational setting.…”
Section: Assessment Instrumentmentioning
confidence: 99%
“…Considerable research has been done to establish the relationships between communication satisfaction and other key organizational variables, including organizational identification (Smidts et al, 2001); membership satisfaction (Taylor, 1997); job satisfaction (Pettit et al, 1997;Trombetta and Rogers, 1988); employee productivity (Clampitt and Downs, 1993); service quality (Snipes, 1996); job performance (Pincus, 1986) (Burmann and Zeplin, 2005), and some have focused on the relationship between internal branding and employees' brand loyalty (Papasolomou and Vrontis, 2006). Drawing upon the social identity theory, Ashforth and Mael (1989) argue that social identification stems from the distinctiveness and prestige of a group.…”
Section: Communication Satisfactionmentioning
confidence: 99%
“…Several researchers have empirically demonstrated the importance of communication climate or its underlying dimensions for employees' commitment (Guzley, 1992; Trombetta and Rogers, 1988; Welsch and LaVan, 1981), organizational identification (Scott, 1997; Smidts, Pruyn and Van Riel, 2001) and job satisfaction (Trombetta and Rogers, 1988). Welsch and LaVan (1981), for instance, found evidence for the relationship between communication variables and organizational commitment: participative decision‐making, motivation (i.e.…”
Section: Organizational Identification In Mergers: Antecedents and Comentioning
confidence: 99%